Frenzied Fiction - Leacock, Stephen, 1869-1944 (Salt Lake City, UT : Project Gutenberg, 2005)
"Frenzied Fiction" by Stephen Leacock is a collection of humorous essays and stories written during the late 19th century. The book presents a satirical look at various aspects of life, society, and human behavior, employing Leacock's signature wit and comedic style. The opening chapter hints at themes of espionage, delusion, and absurdity, providing a playful critique of spies and their dramatic lifestyles, with a focus on the exaggerated self-importance of the protagonist. The opening of "Frenzied Fiction" introduces us to a self-proclaimed spy who relishes in the mystery and intrigue surrounding his supposed profession. As he shares his experiences, we see the comedic elements emerge through his exaggerated tales of subterfuge, his interactions at hotels where he is both feared and revered, and his humorous commentary on the nature of espionage. The protagonist's self-importance and the absurdity of his supposed adventures set the stage for a humorous exploration of the spy genre, while the first chapter hints at the satirical nature of the essays that follow in the collection. (This is an automatically generated summary.)
My revelations as a spy -- Father Knickerbocker: a fantasy -- The prophet in our midst -- Personal adventures in the spirit world -- The sorrows of a summer guest -- To nature and back again -- The cave man as he is -- Ideal interviews -- The new education -- The errors of Santa Claus -- Lost in New York -- This strenuous age -- The old, old story of how five men went fishing -- Back from the land -- The perplexity column as done by the jaded journalist -- Simple stories of success, or How to succeed in life -- In dry Toronto -- Merry Christmas.
Release date is 2005-07-01
Produced by Gardner Buchanan, and David Widger
Keywords: Humorous stories, Canadian